Hydroponics Management System Based Internet of Things - Mohd Razif, Mohamad Haziq; Hussin, Mohamad Zhafran; Md Sin, Nor Diyana; Zainuddin, Hedzlin; Abdul Shukor, Saiful Firdaus (2020)
Nowadays, planting by using soils seems no more relevant as in the year of 1600th scientists had found an alternative method of growing plants much more faster which by using only water as a planting medium. Years by years, this method had been improvised until today but only focusing in the industrial sector and most of them only able to monitor the condition of plant. Hydroponic Management System Based Internet of Things is a project that combines biology and electrical engineering knowledge where the growth of a specific species of plant is being monitored and controlled based on their optimum and ideal factors such as the presence of water as planting medium, surrounding temperature, relative humidity, light intensity and also the pH of water. This product believes that if all the five parameters of plants could be controlled and maintained based on the requirements of each species of plant, the best quality of plant productivity could be produced. In this project, analog sensors are used to sense the condition of a selected species of plant such as the water level, surrounding temperature, etc. and all the value of parameters will be displayed on LCDs and also will be uploaded through the Internet of Things (IoT) application - ThingSpeak. To maintain a constant value of parameters, a few output components will be used if the values are out of their range. Commonly, hydroponics only involved in industrial sector, but this project will bring it into home so that everybody will be able to plant.